Elimination of Congo Red Dye from Industrial Wastewater Using Teucrium polium L. as a Low-Cost Local Adsorbent - Nasser A. Alamrani; Hatem A. AL-Aoh (Adsorption Science & Technology)
A novel adsorbent prepared from the leaf powder of Teucrium polium L. (TPLLP) was characterized and its ability for adsorption of Cong red (CR) was inspected. Influences of CR concentration, adsorbent dosage, time of agitation, pH of solution, and temperature on the performance of this adsorption were also examined. Three models of kinetic along with three different isotherm models were applied for analyzing the empirical data of this adsorption. Additionally, the thermodynamic constants of were decided. The surface area, pore volume, pore size, and pHZPC of Zn/Cu-TPLLP were found to be 2.6436 m2.g-1, 0.013317 cm3.g-1, 527.393 Å, and 8.8, respectively. The achieved outcomes indicate the positive influence of temperature, concentration of CR in the range of 20 to 900 mg/L, adsorbent mass in the range of 0.005 to 0.02 g, time of adsorption from 0 to 120 min, and pH from 5.5 to 8.5. Models of the 2nd order with R2≥0.995 and Langmuir with R2≥0.990 were the best among the other kinetic and isotherm models applied in this research. Moreover, superior capacities of 526.32, 666.67, and 909.09 (mg.g-1) were stemmed at 27, 42, and 57°C, respectively. The outcomes of the thermodynamic evidenced that this adsorption is spontaneous and a heat absorber.